Spektrum Pesantren di Tengah Hegemoni Modernisasi - Eman Sulaeman (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
Islamic boarding schools as educational and social institutions have a very large role in shaping the culture / culture of the community. On the other hand, the pressure for modernization, which sometimes carries negative values, also has a very large influence on the formation of community culture. The interpretation of modern values to community culture is sometimes more visible in the